BIMBINGAN BELAJAR BAGI ANAK YANG SULIT DALAM PEMBELAJARAN DI (Kelas 2 SDN 1 Patai Kecamatan Cempaga Kabupaten Kotawaringin Timur - Nurmiati, Nurmiati (Jurnal Studi Agama dan Masyarakat, 2014)
This study aimed to determine and describe the tutoring for children who have difficulty in the classroom 2 SDN 1 Patai Eastern District of Cempaga Kotawaringin . Subjects in this study were teachers who teach in grade 2 SDN 1 Patai Eastern District of Cempaga Kotawaringin . The results of this study indicate that ; a) The problems of childrens learning Grade 2 SDN 1 Patai is when learning begins the child does not have a receptive attitude to learn , there is no motivation for learning , the childs activity is very low or the child is not actively engaged in learning activities , children who have difficulty in learning is not out using appropriate time in learning , and student learning outcomes low